Welfare Assessment Tests and Fetal Maturity - Vigil de Gracia, Paulino (2015)
Intrapartum fetal monitoring: New Concepts. Invasive prenatal diagnostic procedures. Fetal Magnetic Resonance Imaging. Value of lamellar bodies and phospholipids in the Diagnosis of Fetal Lung Maturity.